Philosophy of language A-Z - Tanesini, Alessandra (Philosophy A-Z series., 2007)
Philosophy of Language A-Z offers a broad coverage of theories, debates, concepts, problems and philosophers in the philosophy of language. It consists of concise and accessible entries on each of the key terms and issues in this area of philosophy. Whilst this book is primarily focused on contemporary philosophy of language as discussed within the tradition of analytic philosophy, it also includes entries on historical topics and on key terms and philosophers working in the continental tradition.